Guidelines for landscape and visual impact assessment (Routledge, Taylor & Francis Group, 2013)
"The essential guide to landscape and visual impact assessments for landscape architects from the Landscape Institute and the Institute of Environmental Management and Assessment"-- Provided by publisher.